2013
DOI: 10.1103/physrevd.87.115022
|View full text |Cite
|
Sign up to set email alerts
|

Gluino-driven radiative breaking, Higgs boson mass, muong2, and the Higgs diphoton decay in supergravity unification

Abstract: We attempt to reconcile seemingly conflicting experimental results on the Higgs boson mass, the anomalous magnetic moment of the muon, null results in search for supersymmetry at the LHC within the 8 TeV data and results from B-physics, all within the context of supersymmetric grand unified theories. Specifically, we consider a supergravity grand unification model with non-universal gaugino masses where we take the SU(3)C gaugino field to be much heavier than the other gaugino and sfermion fields at the unific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 115 publications
0
83
0
Order By: Relevance
“…In addition, when µ ≪ M 1,2 , these processes are largely insensitive to other SUSY parameters but higgsino mass µ. Therefore, we do not consider the production of stops and gluino in this paper, which contribute to the fine-tuning in more complicated and model-dependent way [19][20][21][22]. The current constraints on the mass limits of stop and gluino in natural SUSY have been discussed in [28][29][30][31][32][33].…”
Section: Calculations and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, when µ ≪ M 1,2 , these processes are largely insensitive to other SUSY parameters but higgsino mass µ. Therefore, we do not consider the production of stops and gluino in this paper, which contribute to the fine-tuning in more complicated and model-dependent way [19][20][21][22]. The current constraints on the mass limits of stop and gluino in natural SUSY have been discussed in [28][29][30][31][32][33].…”
Section: Calculations and Discussionmentioning
confidence: 99%
“…(1.1), µ and m Hu must be of the order of ∼ 100 − 200 GeV, which implies light higgsinos. At the same time, the electroweak gaugino mass parameters M 1,2 are preferred to be of the similar order as the heavy gluino mass parameter M 3 and large Higgs-stop trilinear coupling A t is JHEP02(2014)049 needed [19][20][21][22]. Hence, generically we have µ ≪ M 1,2 and the mass splittings between the lightest chargino and the lightest two neutralinos at leading order are determined by [27] …”
Section: Introductionmentioning
confidence: 99%
“…[22]. 2 In addition to the usual parameters, the gluino soft mass M 3 is allowed to float at the GUT scale, as shown in Table 2.…”
Section: Gut-defined Models and Experimental Constraintsmentioning
confidence: 99%
“…The 8 TeV run has provided strong lower bounds on chargino and slepton masses, in particular when interpreted in the framework of simplified model spectra (SMS) [34]. However, several studies have shown [19,22,23,28,29] that if the experimental limits provided by the CMS and ATLAS collaborations are reinterpreted and applied to more general MSSM scenarios the 8 TeV LHC results can only constrain a small part of the available parameter space, so that ample room still remains to attribute a supersymmetric (SUSY) origin to δ (g − 2) µ .…”
Section: Introductionmentioning
confidence: 99%
“…Many recently proposed models which stay within the MSSM framework involve rather split spectra, e.g. heavy coloured, light non-coloured SUSY particles [20][21][22][23], heavy third family, lighter first and second family [24], non-universal gaugino masses [25,26], large Higgsino masses and large stop mixing from more generic gauge mediation [27].…”
Section: Introductionmentioning
confidence: 99%